The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.aller.2017.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Serum periostin is not related to asthma predictive index

Abstract: Serum periostin levels were no significantly different between wheezer pre-schoolers with positive and negative API. More studies are needed to confirm this finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
0
7
0
2
Order By: Relevance
“…Serum periostin levels showed no difference in preschool wheezers according to the API. 35) The API is inexpensive, less invasive, and has been validated by several studies, 5,20) and the diagnostic accuracy in this study is quite fair, so it can be used for asthma screening in preschool children. The strength of this study is that, unlike other studies, spirometry, AHR, FeNO, and BDR were evaluated in preschool children.…”
Section: Discussionmentioning
confidence: 68%
“…Serum periostin levels showed no difference in preschool wheezers according to the API. 35) The API is inexpensive, less invasive, and has been validated by several studies, 5,20) and the diagnostic accuracy in this study is quite fair, so it can be used for asthma screening in preschool children. The strength of this study is that, unlike other studies, spirometry, AHR, FeNO, and BDR were evaluated in preschool children.…”
Section: Discussionmentioning
confidence: 68%
“…However, they have also addressed a concern regarding the possible confounder effect of the linear growth on serum periostin levels during the early‐childhood phase. Castro‐Rodriguez et al 14 have performed a case‐control study in preschoolers with recurrent wheezing episodes and compared periostin levels according to their asthma predictive index result. No significant difference was found in periostin levels between children with positive and negative asthma predictive index.…”
Section: Discussionmentioning
confidence: 99%
“…Other inflammatory biomarkers e.g., periostin, CC16 and YK-40, were also tested in population with positive and negative original API. A study done in 48 Chilean preschoolers (aged 24–71 mo) reported no significant differences in serum periostin levels for those with positive API and negative API; and no significant correlation between serum periostin levels and peripheral blood eosinophils (40). Also, no difference in level of serum CC16 levels for preschoolers with a positive API and negative API were found in the same population (41).…”
Section: Predictive Models For Prognostic or Diagnostic Toolsmentioning
confidence: 99%